Structural Analysis and Dynamic Performance Research of Redundant Diaphragm Coupling - Xuezhi Li; Meng Chen (Jixie chuandong, 2019)
Aiming at the problem of the diaphragm coupling is affected by snap loads which lead to diaphragm fatigue broken and fracture failure， the structural and dynamic performance of the redundant diaphragm coupling are carried out. The overall structure of the redundant diaphragm coupling is designed， and the finite element analysis model of diaphragm disk is established， the optimum thickness of the diaphragm meets the design requirement is obtained by calculating. Then， the safety factor of the redundant structure is verified based on the strength analysis of redundant structure of diaphragm coupling， and the transmission of the torque can be realized. Finally， the frequency response curve is obtained based on the dynamic performance research of the diaphragm coupling. The results can provide the effective basis for the analysis of mechanical transmission devices in this field.